Slowdown. Una questione di classe? - Meloni, Pietro; Valzania, Andrea (SocietàMutamentoPolitica, 2023)
What does it mean to slow down and who can do it? In recent years, the need to decelerate to avoid environmental and social catastrophes has been evoked more and more often. The world runs too fast, we are now unable to act thoughtfully and really enjoy our life, which always flows at greater speed. And yet, we continually dream of slowing down, of rediscovering more authentic, everyday relationships. We dedicate ourselves to new hobbies, we learn to work with our hands, we plant vegetables on the terrace, we allow ourselves small and short holidays as a moment in which we believe we have regained possession of our existence. But today time has become a privilege and not everyone is allowed to use it. Having time is often a luxury, in the face of thousands of workers who can never slow down. Using the pandemic as the central moment of a suspension of time, we would like to explain what it means to slow down in late capitalist societies and why it is increasingly a question of class. Our slowness, in fact, is always related to the time taken away from someone else.